EVIDENCE FOR NATUROPATHIC AND YOGIC INTERVENTIONS TO AUGMENT THE EFFECTS OF ART CARE AS AN ADJUVANT THERAPY- A PARALLEL MATCHED CONTROL STUDY - MK Nair, Pradeep; M, Sriloy; H, Salwa; D, Sathyanath (International Journal of Clinical and Biomedical Research, 2016)
Background: Complementary and alternative medicine (CAM) is becoming a pillar in the rehabilitative efforts for many people living with HIV AIDS (PLWHA). The efficacy of naturopathic and yoga intervention, a CAM therapy is an area to be explored in rehabilitation of PLWHA. Aim: The present study, a parallel matched control study to was designed to compare the efficacy of naturopathic and yogic interventions as an adjuvant therapy with standard Antiretroviral Therapy (ART) to PLWHA. Methods: Twenty matched subjects were screened for the study based on the criteria: HIV positive subjects aged between 25 to 55 years, both sexes, no secondary infections, under ART care, last CD4 estimate done on June 2014. The intervention group (IG) underwent Naturopathic and yogic intervention along with ART in a HIV sanatorium for a month followed by periodical follow up and control group (CG) received only ART. The outcome measure was a change in CD4 count. Results: After the end of 6 month, the IG showed significant changes CD4 cell count (p=3.96E-05). The CG also showed a significant improvement in CD4 cell counts (p= 0.024) but not of the same magnitude as of IG. An independent t-test between the groups has shown that the IG was more significant (p=0.047). Conclusion: The improved levels of CD4 cells in the intervention group suggests that naturopathy and yoga can augment the efficiency of ART care and can be safely prescribed to PLWHA and prescribed as a adjuvant therapy. KEYWORDS: HIV care; Naturopathy; Yoga; ART; CD4 count.